A distributed differentially encoded OFDM scheme for asynchronous cooperative systems with low probability of interception - Li, Zheng; Xia, Xiang-Gen (IEEE transactions on wireless communications, 2009)
Recently, Li, Hwu and Ratazzi have proposed a physical-layer security design to guarantee low probability of interception (LPI) for MIMO systems without relying on upper layer data encryption. The proposed scheme utilizes antenna array redundancy to deliberately randomize the transmitted signals to prevent eavesdropping. Motivated by their idea, in this paper we design a physical-layer transmission scheme to achieve LPI in cooperative systems. There are two major differences in cooperative systems: (1) each relay node may have only one antenna that can not provide antenna array redundancy for signal randomization; (2) there may exist timing errors due to the asynchronous nature of cooperative systems. Considering the two differences, we propose a distributed differentially encoded OFDM transmission scheme with deliberate signal randomization to prevent eavesdropping and exploit the available spatial and frequency diversities in asynchronous cooperative systems. We use diagonal unitary codes to perform the differential encoding in the frequency domain over subcarriers within each OFDM block, or we use general (not necessarily diagonal) unitary codes to perform the differential encoding in the frequency domain across several OFDM blocks. By some deliberate signal randomization, the eavesdropper can not detect the transmitted symbols, while the authorized receiver can perform differential decoding successfully without the knowledge of the channels or the timing errors.